Assessing the social patterning and magnitude of inequalities in sexual violence among young women in Uganda: Findings from 2016 demographic and health survey. Issue 11 (2nd November 2022) - Mutumba, Massy; Bhattacharya, Subarna; Ssewamala, Fred M.
ABSTRACT: Sexual violence (SV) is a significant global public health problem. To develop effectively targeted interventions to prevent SV and allocate resources equitably requires identifying the most vulnerable groups and the magnitude of these social inequities. However, these data are currently lacking. Using the Uganda Demographic and Health Survey, we examined SV among all young women and ever-married young women. We conducted univariate and bivariate analyses to characterise the prevalence and social patterning of SV, and then utilised the World Health Organization Health Equity Assessment Toolkit (HEAT) to assess the magnitude of social inequities in SV. At the national level, 5.5% among all young women and 20.5% of ever-married young women had experienced SV. For all young women, the largest inequities in SV were based on sub-national region of residence. Among the ever-married young women, we found profound education, wealth and place-based inequities in SV, which favoured young women with higher education, in wealthier households, and within central regions of Uganda. Our findings suggest a need for regionally targeted multi-sectoral interventions that take into consideration that multiple intersecting social dimensions such as education, poverty and the safe built environment, to address young women's risk for SV.